Menguatkan Kepemimpinan Inklusif pada Gen Z di Era Digitalisasi melalui Implementasi Nilai-Nilai Pancasila - noor, zuhhar raihan; Firdaus, Muhammad Rizqi (Maliki Interdisciplinary Journal, 2025)
Generation Z has felt the impact of globalization and digitalization which has affecting their ability to lead and communicate. In this era, leadership development based on Pancasila values is very important for Generation Z to uphold morality and justice. The principles of Pancasila such as divinity, humanity, unity, democracy, and social justice provide a solid moral foundation for inclusive leadership is goal-oriented. Inclusive leadership based on the principles of Pancasila will encourage active participation from many circles, encourage cooperation, and create environtment and cooperative. In accordance with Pancasila values, Generation Z can develop a leadership style that is patient, diverse, and respectful of decisions together. This inclusive leadership encourages active participation from all community, focusing on solutions that make sense and benefit the community everyone, as well as strengthening unity. In this way, Generation Z can be believed to be a force of change world without losing national identity and national values. Generation Z can also make decisions that are very beneficial for society and developing adaptive, innovative and inclusive leadership patterns, as well as adhere to a strong national identity and respect values sublime Pancasila.